The transmission of knowledge in South Asia : essays on education, religion, history, and politics - Crook, Nigel (Delhi ; New York : Oxford University Press, 1996)
Contributed essays.
Includes bibliographical references.
Keywords: Education -- South Asia; Educational sociology -- South Asia; Education -- Political aspects -- South Asia